Kinesiotaping versus counterforce brace in the management of lateral elbow tendinopathy - Asmaa F. Abdelmonem; Mariam A. Ameer; Ammar M. AlAbbad; Azza M. Abdelmohsen (Journal of Orthopaedics, Trauma and Rehabilitation)
Purpose: The main purpose of the current study was to assess whether counter force brace (CFB) offers any additional value over Kinesiotaping (KT) in the management of tennis elbow. Materials and Methods: Forty-five females with clinically diagnosed tennis elbow participated in the current study. They were equally assigned into three groups of equal numbers. 12 sessions over 4 weeks of treatment interventions; experimental group A received the traditional physiotherapy program in addition to KT. Group B received the physiotherapy program in addition to the CFB. Group C (Control Group) received the physiotherapy program only. The degree of tennis elbow pain and myoelectrical activities of forearm muscles were measured. Results: There was a statistically significant reduction of pain in the experimental group A (KT) in comparison with the control group (p = 0.000), while a statistically significant reduction of pain (p = 0.000) and improvement of the myoelectrical activities of the forearm muscles (p = 0.000) were detected in the experimental group B (CFB) in comparison with the control group. In addition, the statistically significant reduction of pain (p = 0.000) and improvements in wrist flexors and extensors (p = 0.001 and p = 0.000, respectively) were detected in CFB compared with KT. Conclusion: Compared to KT or a physical therapy program alone, the use of CFB in the treatment of lateral elbow tendinopathy may be beneficial, especially in reducing pain and enhancing the muscle activities of the elbow flexors and extensors.